Scrum Maturity Level Evaluation and Improvement Recommendation: Case Study on ABC Application - Alcredo Simanjuntak; Eko K. Budiardjo; Kodrat Mahatma (Ikatan Ahli Informatika Indonesia (IAII), 2023)
Bank XYZ, one of the digital banking in Indonesia, has a digital product ABC for customers to complete online banking transactions. Bank XYZ uses Scrum as the methodology to develop ABC. Several problems were found in the process related to the delay in the release process. The achievement of sprint goals from May to December 2021 is only 6%. This fact allegedly caused some frequent release delays. To resolve the root causes, mixed-method research was conducted to provide recommendations for improving the implementation of Scrum. The Scrum Maturity Model questionnaires were distributed to several Scrum teams, followed by interviews with several roles that were used to validate the results. The key process area rating formula of the Agile maturity model was used to decide the maturity level. After the maturity level result was obtained, recommendation practices were generated from the not well-implemented practice. This case-based research shows that Bank XYZ reached maturity level 2 for ABC development. Bank XYZ has implemented 78 out of 79 practices, however, 28 practices need improvement and one practice needs to be applied. Objectives of maturity levels group recommendation practices. The combination of Scrum best practices and empirical practices from previous research generated those practices. This research was intended to give general recommendations on how to improve Scrum implementation and on how to resolve release time problems by enhancing Scrum in Bank XYZ empirically.